Implementation of Batu Kuning Baturaja Terminal Based on the Regulation of the Minister of Transportation Number 40 of 2015 concerning Service Standards for the Implementation of Road Transportation Passenger Terminals - Nora Soraya Sinabutar (Administrative and Environmental Law Review, 2020)
The effectiveness of terminal operation is related to how far the government carries out the terminal functions as it should be. To determine the effectiveness of the Batu Kuning terminal operation in Baturaja, based on the Minister of Transportation Regulation Number 40 of 2015 concerning Standard Services for the Implementation of Road Transportation Passenger Terminals, in this study using a normative-empirical legal approach. Furthermore, the effectiveness of the operation of the Batu Kuning terminal can be seen through four things in general, namely accessibility, facilities, comfort and security of the terminal itself in accordance with the Minister of Transportation Regulation Number 40 of 2015 that the operation of the terminal is obliged to provide safety, security, comfort, convenience, and equality service for the community. Batu Kuning Terminal as a class 3 type A terminal in Baturaja cannot be said to be effective because the accessibility, facilities, comfort and safety of the Batu Kuning terminal are inadequate because the indicators in the Minister of Transportation Regulation Number 40 of 2015 are not available. So it is necessary to add and repair Batu Kuning terminal facilities, both main facilities and task support facilities in order to increase the effectiveness of the terminal, not only the duty of law enforcement officers, but all parties using the road must cooperate with each other, be it AKAP, AKDP, ANGKOT drivers. and ANGDES, passengers, and all the people in the Batu Kuning terminal have the obligation to work together to support the operation of the Batu Kuning terminal to run effectively.